Chrysophanol-8-O-glucoside, an Anthraquinone Derivative in Rhubarb, Has Antiplatelet and Anticoagulant Activities - Eun Ji Seo; Tran Minh Ngoc; Sun-Mee Lee; Yeong Shik Kim; Yi-Sook Jung (Elsevier, 2012)
Rhubarb is a widely used traditional medicine and has been reported to elicit a number of biological effects including anti-inflammatory and antiplatelet effects. In the present study, we investigated the effects of anthraquinone derivatives isolated from rhubarb on platelet activity. Of four anthraquinone derivatives isolated from rhubarb examined, chrysophanol-8-O-glucoside (CP-8-O-glc) was found to have the most potent inhibitory effect on collagen- and thrombin-induced platelet aggregation. CP-8-O-glc-treated mice showed significantly prolonged bleeding times. Furthermore, CP-8-O-glc was found to have a significant inhibitory effect on rat platelet aggregation ex vivo and on thromboxane A2 formation in vitro. In coagulation tests, CP-8-O-glc did not alter prothrombin time, and it prolonged the activated partial thromboplastin time. However, CP-8-O-glc only inhibited platelet phosphatidylserine exposure, but not exert direct inhibition on intrinsic factors. This study demonstrates the antiplatelet and anticoagulant effects of CP-8-O-glc and suggests that this compound might be of therapeutic benefit for the prevention of platelet-related cardiovascular diseases. Keywords:: chrysophanol-8-O-glucoside, anthraquinone derivative, antiplatelet, anticoagulant, rhubarb